Sexual Alcohol Expectancies, Alcohol Intoxication, and Sexual Behavior in MSM: An Experience Sampling Study. - Murray, Grace E.; Palfai, Tibor P.; Kratzer, Maya P. L.; Maisto, Stephen A.; Beckius, Brooke Z.; Simons, Jeffrey S. (AIDS & Behavior, 2024)
Despite advances in prevention and treatment, the transmission of human immunodeficiency virus remains a significant problem in the United States, especially among men who have sex with men (MSM). Alcohol use can promote risky sexual decisions, and alcohol expectancies may influence the role of alcohol in decision making. The present secondary analysis tests the moderating role of sexual alcohol expectancies (SAEs) in the relation between daily alcohol intoxication and sexual behavior in a sample of 248 moderate- to heavy-drinking MSM. SAEs were assessed with the Sexual Alcohol Expectancies Questionnaire at baseline, followed by two 23-day bursts of ecological momentary assessment including self-initiated morning assessments of sexual behavior and the prior night's perceived intoxication, as well as nine daily random alcohol assessments. Multilevel modeling showed that SAEs moderated a curvilinear association between intoxication and anal intercourse with a condom such that the relation between daily intoxication and anal intercourse with a condom is a more pronounced inverted u-shape among individuals with strong SAEs, and this moderation effect was not seen for condomless anal intercourse (CAI). While SAEs do appear to influence the association between intoxication and sexual behavior in MSM, they do not appear to moderate the association between alcohol intoxication and CAI.